The Patellar Resurfacing in Total Knee Prosthesis: Indications for Bone Stock and Patellar Morphology - Molfetta, Luigi; Casabella, Andrea; Palermo, Augusto (Frontiers in Medicine, 2021)
The patellar resurfacing is still a controversial and unresolved problem. The choice to use the patellar resurfacing in the total knee prosthesis (TKP) is decided by the surgeon's experience; he analyzes the thickness, the shape, consumption of the surface and he chooses the use of patellar resurfacing or to limit itself to cheiloplasty , denervation, or often to the release of the lateral wing ligament. He also assesses the metabolic state of the bone linked to Osteporosis and the potential fragility of the joint and kneecap in particular. Bone loss after total knee arthroplasty (TKP) may lead to periprosthetic fractures that are associated with significant costs (morbidity, economic, etc.) and pose a challenge to operative fixation.The literature doesn’t express a definitive judgment on the two options, since the results can be overlapped on average. Each option has advantages and disadvantages to be considered in the overall balance of the patellar operation. In reality, however, this technical choice requires more consolidated decision-making criteria so as to minimize the incidence of post-surgical femoral-patellar pain syndrome, the second cause of failure, which frequently leads to revision of the implant. The balance between experience and evidence can be a compromise in the choice of surgery. The experience documented in the literature must identify the parameters capable of constructing an algorithm aimed not only at the secondary resurfacing rate, but at the overall clinical evaluation. This has implications also for the rehabilitation of these patients after surgery.